Metastatic Pancreatic Adenocarcinoma Manifesting as Otomastoiditis and Collet–Sicard Syndrome - Alexander Herbert; Ji-Suk Moon; Aaron Domack; Alexander Velazquez; David Ward; Martin Manuel Cearras (Annals of Internal Medicine: Clinical Cases)
Otomastoiditis is not prevalent in immunocompetent adults and in some cases can be caused by insidious malignancies of the temporal bone. Collet–Sicard syndrome (CSS) is a constellation of symptoms associated with unilateral lower cranial nerve deficits that can occur in the setting of radiologically elusive temporal bone malignancies. We present a rare case of an adult man with temporal bone biopsy–confirmed pancreatic cancer that initially presented with otomastoiditis and CSS. This case demonstrates how malignancy should remain a top differential diagnosis for clinicians who encounter immunocompetent adults with otomastoiditis, even when unsupported by advanced imaging modalities.